Bullying among adolescents in residential programs and in public school: the role of individual and contextual predictors. Issue 2 (11th April 2016) - Wright, Michelle F.
Abstract : Purpose: – The purpose of this paper is to compare rates of bullying and victimization between 50 adolescents in residential programs and 50 control adolescents in regular public schools. Individual (i.e. peer attachment) and contextual predictors (i.e. parenting styles, school belongingness) were also examined, and investigated in relation to bullying involvement. Design/methodology/approach: – Participants were matched based on ethnicity, gender (all male), and parents' income. They completed questionnaires on their bullying involvement, peer attachment, perceived parenting styles of their parents, and school belongingness. Findings: – The findings revealed that adolescents from residential programs had higher rates of bullying and victimization, experienced more permissive parenting styles, had lower peer attachment, and poorer school belongingness when compared to control adolescents. The positive relationship between permissive parenting and bullying was stronger for boys from residential programs. In addition, peer attachment and school belongingness were more negatively related to bullying among control boys. Similar patterns were found for victimization. Differences were also found concerning the relationship of the individual and contextual predictors to adolescents' bullying and victimization across the two groups. Originality/value: – These results underscore the importance of studying bullying and victimization among adolescents in secure settings, particularly residential programs.